2022
DOI: 10.1021/acs.nanolett.2c01943
|View full text |Cite
|
Sign up to set email alerts
|

Small Charging Energies and g-Factor Anisotropy in PbTe Quantum Dots

Abstract: PbTe is a semiconductor with promising properties for topological quantum computing applications. Here, we characterize electron quantum dots in PbTe nanowires selectively grown on InP. Charge stability diagrams at zero magnetic field reveal large even−odd spacing between Coulomb blockade peaks, charging energies below 140 μeV and Kondo peaks in odd Coulomb diamonds. We attribute the large even−odd spacing to the large dielectric constant and small effective electron mass of PbTe. By studying the Zeeman-induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Further study of the devices under a limited magnetic field showed tha PbTe CQDs exhibit a strong Rashba spin-orbit interaction. In 2022, Kate et al proposed a device structure for selectively growing PbTe CQDs on InP and characterized the CQD devices in both zero and finite magnetic fields (Figure 2e,f) [37]. The Coulomb charge stability analysis revealed large even-odd spacing at zero magnetic field.…”
Section: Pbte Cqd Photodetectorsmentioning
confidence: 99%
“…Further study of the devices under a limited magnetic field showed tha PbTe CQDs exhibit a strong Rashba spin-orbit interaction. In 2022, Kate et al proposed a device structure for selectively growing PbTe CQDs on InP and characterized the CQD devices in both zero and finite magnetic fields (Figure 2e,f) [37]. The Coulomb charge stability analysis revealed large even-odd spacing at zero magnetic field.…”
Section: Pbte Cqd Photodetectorsmentioning
confidence: 99%
“…Here, we present the PbTe-Pb hybrid as a new planar JJ material platform for exploring topological superconductivity and other potential applications, such as gate tunable qubits. While the PbTe-Pb hybrid has recently been proposed in its nanowire form as a Majorana candidate with promising experimental progress, in this paper, we realize its 2DEG version, motivated by the Majorana proposals for topological planar JJs. , Selective area growth (SAG) of PbTe film has been previously achieved on InP, a substrate that is lattice-mismatched with PbTe . In this work, the SAG PbTe film is grown on a lattice-matched substrate to minimize the disorder.…”
mentioning
confidence: 99%
“…The method of selective area growth (SAG) potentially removes this roadblock by allowing large-scale lithographic control of planar nanowire growth. Already, key device concepts based on SAG nanowires have been realized, such as field effect transistors (FETs), , nanowire Hall bars, , quantum interferometers, , hybrid superconducting devices, ,, and quantum dots . So far, however, the focus has been on proof-of-principle experiments based on a few devices.…”
mentioning
confidence: 99%